2010
DOI: 10.1117/1.3492411
|View full text |Cite
|
Sign up to set email alerts
|

Engineered low-dimensional nanomaterials for sensors, actuators, and electronics

Abstract: In this paper, a general method of producing zero-dimensional (0-D) and one-dimensional (1-D) nano-structures by adjusting only one parameter in the process of production is investigated. To further study the result of small-scale effects, a quantitative characterization for the specific surface area of 1-D nanostructure is proposed. And the characterization method could be integrated into the nano-systems to reflect useful parameters for the analysis of nanomaterials. These two methods mentioned above could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…16,44,67 Yu et al 45 reported the efficacy of a graphene/Ag nanocomposite in bacteria. 39 Recently, Fiorillo et al 15 using large GO flakes, observed a dose-dependent inhibition of tumor sphere formation; interestingly, neither small nor large GO flakes affected the viability of the bulk non-CSC population of the MCF7 cells indicating the selectivity of GO toward CSCs of ovarian, prostate, pancreatic, and lung cancers as well as glioblastoma. This is the first comprehensive study showing the efficacy of GO, rGO, rGO-Ag nanocomposite, and AgNPs.…”
Section: Analysis Of Surface Morphological Features Of Go Rgo and Rmentioning
confidence: 99%
See 1 more Smart Citation
“…16,44,67 Yu et al 45 reported the efficacy of a graphene/Ag nanocomposite in bacteria. 39 Recently, Fiorillo et al 15 using large GO flakes, observed a dose-dependent inhibition of tumor sphere formation; interestingly, neither small nor large GO flakes affected the viability of the bulk non-CSC population of the MCF7 cells indicating the selectivity of GO toward CSCs of ovarian, prostate, pancreatic, and lung cancers as well as glioblastoma. This is the first comprehensive study showing the efficacy of GO, rGO, rGO-Ag nanocomposite, and AgNPs.…”
Section: Analysis Of Surface Morphological Features Of Go Rgo and Rmentioning
confidence: 99%
“…For several decades, AgNPs have been of considerable interest in several areas of research, including optics, electronics, magnetics, mechanics, catalysis, energy science, nanobiotechnology, and nanomedicine -particularly as antimicrobial agents for diagnostic purposes. 36 AgNPs also have potential applications in surface enhanced Raman scattering, 37 catalysis, 38 nanoscale electronics, 39 and imaging. 40 Several studies have reported the use of AgNPs as anticancer 41 and antiangiogenic agents in retinal endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 165,166 ] BAW resonators consist of a piezoelectric film placed between two metal electrodes, inducing an acoustic wave that propagates vertically along the bulk of the piezoelectric film and forms a standing wave between the electrodes. The piezoelectric film plays an important role in MEMS systems, such as optical attenuators, [ 167–171 ] scanning mirrors, [ 172–176 ] and energy harvesters [ 177–186 ] and transducers. [ 187–190 ] To increase communication frequency to the terahertz range, small‐scale integrated photonic resonators have been studied and demonstrated, driving exploration at both the signal transmitter and receiver sides.…”
Section: Photonic Resonatormentioning
confidence: 99%
“…[ 31 ] These energy systems are designed to meet the requirements of harvesting energy from diverse sources and converting it into electricity by utilizing multiple mechanisms. [ 32–34 ] Self‐powered electronic devices require various energy sources for optimal performance, and hybrid devices are a promising solution for harvesting multiple types of energy simultaneously. While PENGs and TENGs have distinct differences in design and operation, researchers have found that combining these technologies can significantly improve energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%